Analysis of the Biosafety System for Biotechnology in Kenya: Application of a Conceptual Framework - Traynor, Patricia L.; Macharia, H. K. (International Service for National Agricultural Research, 2003)
Kenya is a signatory to the Cartagena Protocol for Biosafety, which offers a set of guidelines regarding the safe handling and use of genetically modified organisms (GMOs). The Protocol also requires signatory countries to develop a regulatory framework and the capacity (in terms of people, expertise, and technology) to undertake risk assessments with regard to the development and use of GMOs. Building capacity in biosafety is thus strategically important for signatory countries, both in meeting obligations under the Protocol and in advancing the successful integration of biotechnology into agricultural research and production. This country report analyses the status of the national biosafety system in Kenya and also serves to test the suitability of the framework. The report's findings and recommendations may serve as the basis for discussions to strengthen and adapt the biosafety system in Kenya.